2022
DOI: 10.3389/fpsyt.2022.1005523
|View full text |Cite
|
Sign up to set email alerts
|

Low carbohydrate and psychoeducational programs show promise for the treatment of ultra-processed food addiction

Abstract: Food addiction, specifically ultra-processed food addiction, has been discussed in thousands of peer-reviewed publications. Although 20% of adults meet criteria for this condition, food addiction is not a recognized clinical diagnosis, leading to a dearth of tested treatment protocols and published outcome data. Growing numbers of clinicians are offering services to individuals on the basis that the food addiction construct has clinical utility. This audit reports on clinical teams across three locations offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Thus, TWS appears to capture more associations between WS and UPFA symptoms than the NWSS. This may be because the NWSS calculation is more likely to categorize individuals as positive for WS if they have maintained weight loss, which has been associated with lower UPFA symptoms in prior research [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TWS appears to capture more associations between WS and UPFA symptoms than the NWSS. This may be because the NWSS calculation is more likely to categorize individuals as positive for WS if they have maintained weight loss, which has been associated with lower UPFA symptoms in prior research [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TWS appears to capture more associations between WS and UPFA symptoms than the NWSS. This may be because the NWSS calculation is more likely to categorize individuals as positive for WS if they have maintained weight loss, which has been associated with lower UPFA symptoms in prior research [39]. The exception for criterion 2 could relate to the association noted above between NWSS and increased endorsement of binge eating behavior, as this may involve a substantial amount of time obtaining, eating, and recovering from UPF intake.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies have suggested a low carbohydrate high-fat diet as potential metabolic therapy for the management of binge eating and ultra-processed food addiction 19,20 . Animals were fed with either normal chow or a KD and given free access to two bottles each of water and 10% sucrose for four consecutive weeks.…”
Section: The Ketogenic Diet Does Not Affect Sucrose Consumptionmentioning
confidence: 99%
“…Altered gene expression 17 , neurotransmitter levels 18 and metabolic profile of the brain cells 11 by KD are some suggested molecular mechanisms driving its neuroprotective effects. Recent studies have suggested KD as a potential dietary intervention for the management of ultraprocessed and palatable food addiction 19,20 .…”
Section: Introductionmentioning
confidence: 99%